Navigating Politics: How Non-Elite Women in Eastern Indonesia Counteract Dynastic Power - Zainal, Asliah; Zainal, Muh. Asrianto; Rustan, Ahmad Sultra; Rezki, Anita; Syam, Ananta Prayoga Hutama; Setianingsih, Dwi (Jurnal Ilmiah Peuradeun, 2025)
Amid the entrenched grip of dynastic and oligarchic political power, non-elite women politicians are developing innovative strategies to garner public support. This study examines how non-elite women navigate structural and cultural to confront dynastic and oligarchic politics within the Southeast Sulawesi parliament during the 2019 and 2024 elections. The research focuses on three regions—the Kendari City Regional House of Representatives (DPRD), the Konawe DPRD, and the South Konawe DPRD—where non-elite women have secured more electoral victories than their elite counterparts, despite the strong presence of dynastic politics at both executive and legislative levels. Data were collected through interviews with women politicians and their campaign teams, as well as documentation of campaign billboards and campaign shadowing. Using a political anthropology approach, this study reveals that non-elite women politicians strategically identify safer voter bases, build cohesive teams, and cultivate grassroots loyalty. While their overall influence remains limited, they effectively navigate and counter the intrigues of dynastic and oligarchic politics. The study highlights how their electoral success contributes to reducing class disparities and gender gaps, fostering gradual political change at both micro and macro levels.